Insight into the evolution of Vibrio vulnificus biotype 3's genome - Efimov, Vera; Danin-Poleg, Yael; Raz, Nili; Elgavish, Sharona; Linetsky, Alex; Kashi, Yechezkel (Frontiers in Microbiology, 2013)
Vibrio vulnificus is an aquatic bacterium and an important human pathogen. Strains of V.vulnificus are biochemically classified into three biotypes. The newly emerged biotype 3 appears to be rather clonal and geographically restricted to Israel, where it caused an outbreak of wound infections and bacteremia. To understand the evolution of the bacterium's genome, we sequenced and analyzed the genome of biotype 3 strain VVyb1(BT3), and then conducted a microbial environmental survey of the hypothesized niche from which it probably evolved. The genome of this environmental isolate revealed higher similarity to the published biotype 1 genomes of clinical strains (90%) than to the environmental strains (87%), supporting the virulence of the biotype 3 group. Moreover, 214 of the total 5361 genes were found to be unique to strain VVyb1(BT3), having no sequence similarity to any of the known genomes of V.vulnificus; 35 of them function in DNA mobility and rearrangement, supporting the role of horizontal gene transfer in genome evolution. Interestingly, 29 of the ‘unique’ genes had homologies among Shewanella species. In a survey conducted in aquaculture ponds in Israel, we successfully co-isolated Shewanella and V.vulnificus from the same niche, further supporting the probable contribution of Shewanella to the genome evolution of biotype 3. Indeed, one gene was found in a S.algae isolate. Surprisingly, molecular analysis revealed that some of the considered unique genes are harbored by nonsequenced biotype 1 strains isolated from the same environment. Finally, analyses of the biotype 3 genome together with the environmental survey suggested that its genome originated from a biotype 1 Israeli strain that acquired a rather small number of genes from other bacterial species in the niche, such as Shewanella. Therefore, aquaculture is likely to play a major role as a man-made ecological niche in bacterial evolution, leading the emergence of new pathogenic groups in V.vulnificus.